2021
DOI: 10.3389/fgene.2021.625236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Stromal-Immune Score–Based Genes in Hepatocellular Carcinoma Microenvironment

Abstract: A growing amount of evidence has suggested the clinical importance of stromal and immune cells in the liver cancer microenvironment. However, reliable prognostic signatures based on assessments of stromal and immune components have not been well-established. This study aimed to identify stromal-immune score–based potential prognostic biomarkers for hepatocellular carcinoma. Stromal and immune scores were estimated from transcriptomic profiles of a liver cancer cohort from The Cancer Genome Atlas using the ESTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These populations of cells often engage in cooperative or competitive interactions that facilitate tumor growth, progression, metastasis, as well as evasion from the host immune system [ 38 , 39 ]. The stromal score is derived from the expression levels of genes associated with non-cancerous stromal cells surrounding tumors [ 40 ]. A higher stromal score typically indicates a greater amount of stromal cell infiltration within the tumor microenvironment, which may suggest a better prognosis due to an increased presence of immune cells that can target cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These populations of cells often engage in cooperative or competitive interactions that facilitate tumor growth, progression, metastasis, as well as evasion from the host immune system [ 38 , 39 ]. The stromal score is derived from the expression levels of genes associated with non-cancerous stromal cells surrounding tumors [ 40 ]. A higher stromal score typically indicates a greater amount of stromal cell infiltration within the tumor microenvironment, which may suggest a better prognosis due to an increased presence of immune cells that can target cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have employed the ESTIMATE algorithm to infer proportion of infiltrating immune and stromal cells in the tumor samples, which highlighted reliability and effectiveness of prognosis prediction according to TME signatures and the predictive advantage of TME scores than other single biomarkers. 19 , 20 Based on methodology of WGCNA and a machine-learning method LASSO-Cox, we conducted a dimension-reduced screening for gene expression matrix from TCGA-LUSC samples and a simplified model containing 6 gene signatures (TGM2, C11orf96, PLAAT4, PNCK, KLF5 and C4BPA) was generated.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that HCC patients with high expression of LCK had higher immune scores. The higher the immune score is, the higher the objective response rate of HCC patients to ICIs [ 61 , 62 ]. Activation and maturation of T cells can increase the sensitivity of HCC patients to ICIs [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%